Evaluation of professıonal ethics piınciples by candidate teachers red fame - Şahan, Gülsün; Şahan, Gülsün (Journal of Education and Training Studies, 2018)
The aim of this study is to evaluate the teaching ethics principles according to the opinions of the prospective teachers. From the teaching profession ethics principles of the students, the positive and negative aspects of professionalism, service, responsibility, justice, equality, ensuring a healthy and safe environment, morality, honesty, truth and trust, impartiality, professionalism and continuous improvement, specimens were asked to explain how they would behave when they would be teachers and the answers were evaluated. Qualitative research method was used in the research and students' opinions were taken with semi-structured interview forms. Bartin Faculty of Education was formed from a total of 54 students in the 4th grade with easily accessible sample from the sampling group for the study group. The opinions of students of 27 science teaching and 27 culture of religion and knowledge of ethics teaching were taken in written form and the content analysis of obtained data was examined. There are negative behaviors of the teacher candidates such as being inadequate in the field, being closed for development, not using the technology, being unprepared for the lesson, being unprepared in terms of lesson related materials while the positive examples are being planned, using new methods and techniques, teaching lesson with real examples, using time efficiently. They think that they will be teachers who are sufficient, self-developed, educating, updating, planned,
Keywords: Ethics; Teaching; Professional ethics; Pre-service teachers